2003
DOI: 10.3171/jns.2003.99.6.1053
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of infarct volume and apoptosis by grafting of encapsulated basic fibroblast growth factor—secreting cells in a model of middle cerebral artery occlusion in rats

Abstract: The grafting of encapsulated BHK bFGF-secreting cells protected the brain from ischemic injury. Encapsulation and grafting of genetically engineered cells such as bFGF-secreting cells is thus thought to be a useful method for protection against cerebral ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
1
22
0
1
Order By: Relevance
“…bFGF is one of the most potent neurotrophic factors for the protection of neurons [1, 2, 27, 29, 38]. We previously demonstrated that grafting of encapsulated bFGF-secreting cells protected against ischemic injury after MCAO in rats by directly exerting cytoprotection through suppression of apoptosis in tandem with enhanced angiogenesis at the border of ischemic infarct [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bFGF is one of the most potent neurotrophic factors for the protection of neurons [1, 2, 27, 29, 38]. We previously demonstrated that grafting of encapsulated bFGF-secreting cells protected against ischemic injury after MCAO in rats by directly exerting cytoprotection through suppression of apoptosis in tandem with enhanced angiogenesis at the border of ischemic infarct [38].…”
Section: Discussionmentioning
confidence: 99%
“…bFGF is one of the most potent neurotrophic factors for the protection of neurons [1, 2, 27, 29, 38]. We previously demonstrated that grafting of encapsulated bFGF-secreting cells protected against ischemic injury after MCAO in rats by directly exerting cytoprotection through suppression of apoptosis in tandem with enhanced angiogenesis at the border of ischemic infarct [38]. Functional recovery after intravenous MSC transplantation in ischemic stroke rats also details the secretion of bFGF from MSCs, which reduces apoptosis and promotes proliferation of endogenous stem and progenitor cells within the peri-infarcted tissue [27, 29].…”
Section: Discussionmentioning
confidence: 99%
“…In mice with a null mutation of bFGF gene, both infarct volume and mortality rates were markedly increased after cerebral ischemia, indicating that endogenous bFGF contributes to protection against ischemic brain damage [12]. Exogenous bFGF administered before cerebral ischemia or several hours after ischemia was shown to reduce the infarction size and improve neurologic function [11,37]. However, little research has been carried out to determine the effect of anesthetics on neurotrophic factor expression.…”
Section: Discussionmentioning
confidence: 99%
“…NGF and BDNF also stimulate phospholipase C (PLC)-protein kinse C (PKC) pathways, which activate survival pathways involving NF-κB and anti-apoptotic members of the Bcl-2 family [46][47][48]. Basic fibroblast growth factor (FGF-2) and VEGF acti- vate the MAP kinase pathway (ERK1/2) through PLC or ras, stimulating production of anti-apoptotic proteins, Bcl-2, cyclic AMP binding protein (CREB) and NF-κB [49,50] (Fig. 6).…”
Section: Neuroprotective Mechanismsmentioning
confidence: 99%